Nasolacrimal duct disorders in children. Part II. Treatment - Sielicka, Danuta; Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Congenital nasolacrimal duct obstruction (CLDO) is considered as common and onerous disorder present at infancy. Over 5% of infants have CLDO affecting one or both eyes. The symptoms of CLDO appear shortly after birth or during the first weeks of life. The main symptoms are: epiphora, ropy, mucous discharge in the conjunctival sac. In conservative treatment a lacrimal sac massage is proposed, though it is not always successful. Topical antibiotics are reserved only if secondary conjunctivitis occurs. Fortunately, most cases resolve spontaneously. However, sometimes nasolacrimal duct probing performed under local or general anesthesia is necessary. Prognosis for probing decreases with the increasing number of probings and the age of the patient. In children, who have failed nasolacrimal duct probing, intubation or balloon catheter dilatation of the nasolacrimal system with or without silicone tubing should be considered. In the case of the upper sac obstructions one can use laser endoscopic dacryocystorhynostomy. If it is still not amenable to opening a endonasal endoscopic dacryocystorhinostomy (EESC-DCR), or traditional external dacryocysto-rhinostomy (EXT-DCR), should be performed.